Performance Analysis Of The Helium Purification System In The Indonesia Experimental Power Reactor. Issue 1 (February 2021) - Irianto, Ign. Djoko; Sriyono,; Bakhri, Syaiful; Dibyo, Sukmanto; Kusumastuti, Rahayu; Kadarno, Purwo
Abstract: Indonesia's experimental power reactor (RDE) is a reactor design based on the high-temperature gas-cooled reactor (HTGR) technology with the power of 10 MWth. According to the reactor safety, helium gas as the primary coolant has to be purified to assure the thermal characteristic. There are several stages of the purification process in the helium purification system (HPS). One stage in the train of HPS for removing N2 and O2 gas from the primary coolant system is the cryogenic unit. The cryogenic unit operates in the temperature about - 196 C. The objective of the research is to analyze the cryogenic unit performance in the helium purification system for removing N2 and O2 gas from the primary coolant system in the design of RDE. The performance analysis has been done by simulation using ChemCAD with variations in mass flowrate in the helium purification system and variations in the concentration of N2 and O2 gas in the helium coolant. The pressure in the cryogenic unit and all units of HPS is set in the same pressure of the primary coolant system is 3 MPa. The result showed that helium can be purified from the impurities N2 and O2 gas about 99 % at the mass flow rate of 0.45 kg/s. This result is important to support the design of HPS for RDE.